The Role of Social Workers in Supporting Children with Autism Spectrum Disorder through Activity Daily Living in East Java: Modeling and Behavior Modification Techniques - Kristiana, Novi; Cipta Utama, Yudi Harianto; Poerwanti, Sari Dewi (UIN Sunan Kalijaga Yogyakarta, 2022)
This article examines the role of social workers in the development of children with Autism Spectrum Disorder (ASD) through Activity Daily Living (ADL), which are essential activities needed to achieve independence and build social functioning. The study employs a qualitative approach with a case study method, focusing on children with ASD at the UPT Perlindungan dan Pelayanan Sosial Asuhan Balita Sidoarjo. The approaches used include Bandura's Modelling technique, which emphasizes learning through observation, and Skinner's behavior modification, which relies on positive and negative reinforcement. The findings indicate that consistent implementation of ADL helps children with ASD understand and adhere to daily routines while also enhancing their interest in social interactions with peers. However, using Modelling and reinforcement techniques also carries risks, such as the emergence of negative behaviors due to uncontrolled emotional reactions when routines are disrupted. On the positive side, ADL training has increased children's independence, such as making beds and drinking independently. However, continued support from social workers remains necessary. The combination of Modelling and behavior modification techniques, applied sequentially or alternately, has proven effective in maximizing the outcomes of ADL training for children with ASD. However, individual adjustments are required based on each child's responses and needs throughout the training process. This study highlights the importance of a comprehensive and adaptive approach in supporting the development of greater independence in children with ASD. Keywords: Autism Spectrum Disorder, Activity Daily Living, Social Workers Artikel ini mengkaji peran pekerja sosial dalam perkembangan anak dengan Autism Spectrum Disorder (ASD) melalui Activity Daily Living (ADL), yang merupakan aktivitas penting yang dibutuhkan untuk mencapai kemandirian dan membangun keberfungsian sosial. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus, yang berfokus pada anak dengan ASD di UPT Perlindungan dan Pelayanan Sosial Asuhan Balita Sidoarjo. Pendekatan yang digunakan termasuk teknik Modelling Bandura, yang menekankan pembelajaran melalui observasi, dan modifikasi perilaku Skinner, yang mengandalkan penguatan positif dan negatif. Temuan menunjukkan bahwa penerapan ADL yang konsisten membantu anak-anak dengan ASD memahami dan mematuhi rutinitas sehari-hari sekaligus meningkatkan minat mereka dalam interaksi sosial dengan teman sebaya. Namun, menggunakan teknik pemodelan dan penguatan juga memiliki risiko, seperti munculnya perilaku negatif karena reaksi emosional yang tidak terkendali ketika rutinitas terganggu. Sisi positifnya, pelatihan ADL telah meningkatkan kemandirian anak, seperti kemampuan merapikan tempat tidur dan minum secara mandiri. Namun, dukungan berkelanjutan dari pekerja sosial tetap diperlukan. Kombinasi teknik pemodelan dan modifikasi perilaku, yang diterapkan secara berurutan atau bergantian, telah terbukti efektif dalam memaksimalkan hasil pelatihan ADL untuk anak-anak dengan ASD. Namun, penyesuaian individu diperlukan berdasarkan respons dan kebutuhan masing-masing anak selama proses pelatihan. Penelitian ini menyoroti pentingnya pendekatan yang komprehensif dan adaptif dalam mendukung pengembangan kemandirian yang lebih besar pada anak-anak dengan ASD. Kata kunci: Autism Spectrum Disorder, Activity Daily Living, Pekerja sosial